PENGENDALIAN BANJIR KAWASAN SIMPANG LIMA SEMARANG - Krissetyatno, Febri Wisda; Budi, Ganang Setyo; Darsono, Suseno; Kodoatie, Robert J. (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Simpang Lima area of Semarang is administration region, education residence, service, and industry which are constructed in the center of Semarang sub district. Center Semarang region is an area where is topographically flat. Industry development, trade, and rapid growth people bring Simpang Lima are of Semarang as the prominent center growth of Semarang city. In addition flood happened in region of Simpang Lima area of Semarang is caused by the lack of drainage performance, high sedimentation, and not yet maximum in flood control using provision of water pumps. There are some scenarios to solve that proble,. the first scenario is by fixing the channels in Simpang Lima are of Semarang in order to increase the capacity of channel flow. This way includes widening the channel, fixing the slope of bottom channel, and scanting the discourtesy of channel flow wall. Second scenario is by making new channel in Simpang Lima cycle, because of the difficult to rehabilitate the existing channel which locates under sidewalk of Simpang Lima cycle, so taken solution to make new channel. The new channel locates under the road of Simpang Lima cycle and uses closed channel type. The third scenario is by maximizing the capacity in Kartini Pump Station. Hope by maximizing the capacity of pump may fasten the process of water disposal from Kampung Kali River to Banjir Kanal Timur River and reduce water level in Simpang Lima area of Semarang drainage channel downstream section.